2021
DOI: 10.1097/brs.0000000000004279
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Dysphagia After Anterior Cervical Discectomy and Fusion

Abstract: Study Design. Multicenter prospective study. Objective. Our aim was to evaluate the incidence and predictors of postoperative dysphagia in patients undergoing anterior cervical discectomy and fusion (ACDF). Summary of Background Data. Dysphagia is a common complication after ACDF that can have significant effect on patients' quality of life, but the frequency of prolonged dysphagia and risk factors are not known. Methods. A multicenter prospective study was undertaken at three academic sites to evaluate patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 18 publications
(68 reference statements)
2
22
0
Order By: Relevance
“…The EAT-10 questionnaire asks patients to rate difficulty in 10 swallowing activities on a 0 to 4 scale, for a total score out of 40. The EAT-10 performs with high internal validity and may capture dysphagia following ACDF more accurately than the Bazaz survey 27…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EAT-10 questionnaire asks patients to rate difficulty in 10 swallowing activities on a 0 to 4 scale, for a total score out of 40. The EAT-10 performs with high internal validity and may capture dysphagia following ACDF more accurately than the Bazaz survey 27…”
Section: Methodsmentioning
confidence: 99%
“…The EAT-10 performs with high internal validity and may capture dysphagia following ACDF more accurately than the Bazaz survey. 27…”
Section: Dysphagia Questionnairesmentioning
confidence: 99%
“…Our incidence rates of dysphagia fall within the ranges of prior estimates ranging from 1.7% to 67%. 11,[28][29][30][31][32][33] One study conducted by Smith-Hammond et al 34 used a similar functional measurement assessment of swallowing and reported a 47% incidence of abnormality on videofluoroscopic assessment 1 week 35 However, they only report 14 of the 170 patients to be reoperative ACDFs. Our study population is entirely representative of reoperative cases.…”
Section: Functional and Clinical Dysphagiamentioning
confidence: 99%
“…Individuals who undergo surgery for cervical spine disease with anterior or posterior access tend to develop oropharyngeal dysphagia, which is often severe during the first month and progressively diminishes in intensity over time [26]. Multivariable analyses have identified smoking status, prior cervical surgery, preoperative C2-C7 angle, preoperative dysphagia, preoperative chronic obstructive pulmonary disease, multilevel surgery, and intraoperative steroid use as significant risk factors for dysphagia after ACDF [26][27][28][29][30]. However, the prospective study by Opsenak et al failed to confirm these findings [31].…”
Section: Risk Factorsmentioning
confidence: 99%